2007
DOI: 10.1063/1.2799738
|View full text |Cite
|
Sign up to set email alerts
|

Probing the phase composition of silicon films in situ by etch product detection

Abstract: Exploiting the higher etch probability for amorphous silicon relative to crystalline silicon, the transiently evolving phase composition of silicon films in the microcrystalline growth regime was probed in situ by monitoring the etch product (SiH4) gas density during a short H2 plasma treatment step. Etch product detection took place by the easy-to-implement techniques of optical emission spectroscopy and infrared absorption spectroscopy. The phase composition of the films was probed as a function of the SiH4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…It is observed that for each deposition condition, U sg is more or less constant over the covered range of SCs. Note that even for the regime of S1, where U sg ϳ 25% only ͑in other words, there is plenty of Si atoms available in the plasma͒, r d still strongly depends on the source gas flow of SiH 4 . At higher SC, r d is expected to saturate at the point where the power P will be rate limiting for the dissociation of SiH 4 .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It is observed that for each deposition condition, U sg is more or less constant over the covered range of SCs. Note that even for the regime of S1, where U sg ϳ 25% only ͑in other words, there is plenty of Si atoms available in the plasma͒, r d still strongly depends on the source gas flow of SiH 4 . At higher SC, r d is expected to saturate at the point where the power P will be rate limiting for the dissociation of SiH 4 .…”
mentioning
confidence: 99%
“…Note that even for the regime of S1, where U sg ϳ 25% only ͑in other words, there is plenty of Si atoms available in the plasma͒, r d still strongly depends on the source gas flow of SiH 4 . At higher SC, r d is expected to saturate at the point where the power P will be rate limiting for the dissociation of SiH 4 . The dependency of r d on P in this regime is studied by the effect of the increase in P from 0.13 to 0.40 mW/ cm 2 for S1 and S2, respectively.…”
mentioning
confidence: 99%
See 3 more Smart Citations